Alendronate delivery on amino modified mesoporous bioactive glass scaffolds to enhance bone regeneration in osteoporosis rats. (5th November 2018) - Wang, Xiao; Zeng, Deliang; Weng, Weimin; Huang, Qinfeng; Zhang, Xiangkai; Wen, Jin; Wu, Jiannan; Jiang, Xinquan
Abstract: The regeneration capacity of osteoporotic bones is generally lower than that of normal bones. Nowadays, alendronate (AL) are orally administrated for osteoporosis due to the inhibition of bone resorption. However, systemic administration of AL is characterized by extremely low bioavailability and high toxicity. In this study, the amino-modified mesoporous bioactive glass scaffolds (N-MBGS) were fabricated by a simple powder processing technique as a novel drug-delivery system for AL. The effects of AL on the osteogenic differentiation of bone mesenchymal stem cells derived from ovariectomized rats (rBMSCs-OVX) were first estimated. The loading efficiency and release kinetics of AL on N-MBGS were investigated in vitro and the osteogenesis of AL-loaded N-MBGS in rat calvarial defect model was detected by micro-CT measurements and the histological assay. Our results revealed that proper concentration of AL significantly promoted osteogenic differentiation of rBMSCs-OVX. The amount and delivery rate of AL were greatly improved through amino modification. Additionally, scaffolds with AL showed better bone formation in vivo, especially for the N-MBGS group. Our results suggest that the novel amino-modified MBGS are promising drug-delivery system for osteoporotic bone defect repairing or regeneration. The experimental schematic of the novel amino-modified MBGS as a promising drug-delivery system for osteoporotic bone regeneration. Graphical Abstract: